2018
DOI: 10.1021/acs.nanolett.8b01001
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Excitonic Circular Dichroism between Wurtzite and Zincblende CdSe Nanoplatelets

Abstract: Nanocrystals (NCs) with identical components and sizes but different crystal structures could not be distinguished by conventional absorption and emission spectra. Herein, we find that circular dichroism (CD) spectroscopy can easily distinguish the CdSe nanoplatelets (NPLs) with different crystal structures of wurtzite (WZ) and zincblende (ZB) with the help of chiral L-or D-cysteine ligands. In particular, the CD signs of the first excitonic transitions in WZ and ZB NPLs capped by the same chiral cysteine are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(125 citation statements)
references
References 58 publications
5
120
0
Order By: Relevance
“…[235] Gao et al also reported crystal structure-dependent CD of l-and d-cysteine stabilized CdSe nanoplatelets. [241] The clearly distinguishable optical properties of wurtzite and zincblend CdSe showed that conformation of chiral ligands strongly affect the surface chirality.…”
Section: Chiral Geometry Of Inorganic Crystalsmentioning
confidence: 99%
“…[235] Gao et al also reported crystal structure-dependent CD of l-and d-cysteine stabilized CdSe nanoplatelets. [241] The clearly distinguishable optical properties of wurtzite and zincblend CdSe showed that conformation of chiral ligands strongly affect the surface chirality.…”
Section: Chiral Geometry Of Inorganic Crystalsmentioning
confidence: 99%
“…As a result, the intriguing circular dichroism (CD) peaks occur in the vicinity of the absorption bands of the colloidal NPs. 21 Recently, chiral ligand capped semiconductor nanodots, [22][23][24][25] nanorods 10,26 and NPLs [27][28][29][30] as well as their core-shell nanostructures have been extensively studied. Like in the case of metallic plasmonic NPs such as Au or Ag, the strong coupling between chiral ligand and achiral semiconductor can induce subsequent chirality transfer from molecules to semiconductor core with an anisotropic factor close to 10 -4 .…”
Section: Introductionmentioning
confidence: 99%
“…[29] The more recently developed method for fabrication of chiral QDs through postsynthesis ligand exchange, dramatically increased the ability to study induced chirality in shaped and heterostructured QDs and extended the range of chiral ligands used in the process. [30] These recent studies shed more light on the mechanisms underlying the induction of chirality. By controlling the morphology of QDs, Tang et al showed the enhanced CD signal from wurtzite CdSe nanorods at certain aspect ratios, which was linked to the anisotropic coupling of the molecular dipole and the anisotropic dipole of the nanorods.…”
Section: Semiconductor Nanorods With Induced Circularly Polarized Lightmentioning
confidence: 99%